On-field performances of female and male field hockey players - A review - Lidor, R.; Ziv, G. (International Journal of Performance Analysis in Sport, 2015)
The main purpose of this study was to review a series of studies (N = 23) on on-field performances of female and male field hockey players. Studies were selected from a computerized search in electronic databases (SPORTDiscus, Google Scholar), as well as from a manual search. Among the main findings that emerged from the studies on female players were that (a) the mean distance covered during a game ranged between 5.5-6.6 km, (b) the individual playing time was approximately 48 min, and (c) the average heart rate (HR) was approximately 170 beats·min-1. For the male players, it was found that (a) the total distance covered per playing position for the duration of the game ranged from ~5,820 m to ~10,000 m, (b) the players spent most of the time and covered most of the distance while performing low- and moderate-intensity activities, and (c) the players' HR was over 75% of HRmax for 90% of the game. Among the methodological and measurement concerns discussed in the article are: the variation in the selection of different locomotion categories, the lack of data on game results and opponent strength, and the presentation of data per individual player and/or per playing position.